Description of two new species of Coeliccia from Vietnam (Odonata: Platycnemididae) - Phan, Quoc Toan; Kompier, Tom (Zootaxa, 2016)
Coeliccia hayashii sp. nov. (holotype male, from Doi waterfall, KaNat, K’Bang district, Gia Lai Province, central Vietnam, deposited in VNMN) and Coeliccia mattii sp. nov. (holotype male and female allotype, from Doi Cao, Loc Tan, Bao Lam district, Lam Dong Province, southern Vietnam, deposited in VNMN) are described. The males of both species are characterized by extensive pruinosity on the thorax.